Imagens alquímicas renascentistas como documentos para a história da ciência - Stagni, Reno (2013)
This paper Will present the scientific facts discussed in the book Conversations on the Plurality of Worlds, written by Bernard Le Boyer de Fontenelle, in 1686, which had a great impact on many issues. To narrate the scientific facts of the time, Fontenelle deals, the book first published in 1686, the form of dialogues between supposedly caught him and a marquese on their evening walks around the castle gardens in the Summer. Both talk about the design of astronomical systems from Ptolomy and Copernicus. The Moon, the planets and the possibility of existence of other worlds like our own, are also discussed during the meetings. Narratives built using a communications strategies and arguments in order to facilitate understanding of abstract and complex astronomical phenomena by means of analogies. With the book, takes part in iniciatives to popularize science, in order to inform and entertain people without impose theories, staying somewhat on the fringes of science academies. In this paper we present the ideas of science contained in the book, trying to recognize, at the same time, the similarities and differences of those groups conveyed by scholars